New testament theology in a secular world: a constructivist work in philosophical epistemology and Christian apologetics - Lampe, Peter (T & T Clark, 2012)
Introduction : indicating the problem -- Stages in the history of thought on the way to constructivism -- The brain as a designer -- Objectivity as intersubjectivity : the interface with sociology of knowledge -- A constructivist sociology of knowledge model -- Implications for theological discourse -- Application of the model to early Christian examples : the new reality of the early Christians -- Rather intellectus intellectui concordat than ens intellectui concordat? : normative reflections on the concept of truth and on intercontextual competition in a pluralistic society -- The prospect for a constructivist theory of historiography -- Appendix: Life after death in selected texts of ancient Judaism